Manajemen Stres dan Work-Life Balance untuk Meningkatkan Kesejahteraan Psikologis dan Produktivitas - Vera Sriwahyuningsih; Ananda Maha Putri; Fitria Ariani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
This Community Service Program aimed to enhance the ability of employees at the Public Works and Spatial Planning Office (PUPR) of Padang City in managing work-related stress and maintaining work–life balance. The training employed Mindfulness-Based Stress Management and Work–Life Balance Mapping approaches, consisting of theoretical sessions, guided breathing relaxation, and planning of balanced work routines. A total of 18 employees participated actively in the program. Evaluation results showed a 35% increase in participants’ understanding based on pre-test and post-test scores. Participants also reported positive behavioral changes, including improved time management and reduced tendency to bring work home. The satisfaction rate reached 94%. The program produced a digital training module and formed a peer support group to sustain the practice. Overall, this activity provided significant benefits for employees’ psychological well-being and productivity.